Physiotherapy students’ academic performance and satisfaction after following a chest physiotherapy course in hybrid mode: a case-control study - Bellini, Raffaella; Rossettini, Giacomo; Letafatkar, Amir; Dell’Isola, Andrea; Battista, Simone (Scientific reports, 2024)
Hybrid e-learning offered flexibility for students who could not attend in-person classes during the COVID-19 pandemic, but its effectiveness in teaching chest physiotherapy remains to be determined. This retrospective case-control study assessed physiotherapy students’ academic performance and satisfaction with a hybrid classroom approach adopted during the COVID-19 pandemic for teaching airway clearance techniques. Physiotherapy students participated in a ‘Critical area and airway clearance techniques’ seminar in person or remotely. The evaluation included a multiple-choice quiz (0–20 points) for theoretical knowledge, a checklist (0–10 points) for practical skills, and a total score (0–30 points). Satisfaction was measured using a 5-point Likert scale. Quartile regression tests calculated median differences, 95% confidence intervals (CIs), and Cohen’s d effect sizes for each assessment component. The analysis included 41 students (54% men, mean age: 23 ± 2.1). The face-to-face group outperformed the remote group in total scores (median difference: 6 [95% CI 2.89; 9.10], effect size: 1.48 [0.72; 2.23]) and practical skills (median difference: 4 [2.31; 5.68], effect size: 2.05 [1.35; 2.76]). However, there was no conclusive difference in theoretical knowledge (median difference: 2 [-0.24; 4.24], effect size: 0.61 [-0.07; 1.29]). Student satisfaction was similar. Physiotherapy students attending the ‘Critical area and airway clearance techniques’ seminar remotely achieved lower scores than their in-person counterparts, highlighting the potential limitations of hybrid teaching for this subject. The mean scores indicated that this method allowed students to acquire the necessary knowledge during the COVID-19 pandemic.